2004
DOI: 10.1111/j.1600-0722.2004.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3,4‐methylenedioxymethamphetamine (‘Ecstasy’) on the jaw‐opening reflex and on the α2‐adrenoceptors which regulate this reflex in the anesthetized rat

Abstract: Bruxism, principally jaw clenching, is frequently observed in users of the recreational drug 3,4-methylenedioxymethamphetamine (MDMA). It has been suggested that during bruxism a reduction of the activity of oral protective reflexes occurs. In this study we investigated the effects of intravenously administered MDMA on the digastric electromyographic responses elicited by orofacial electrical stimulation in the rat. We also assessed the effects of either the administration of a single dose (20 mg kg(-1), s.c.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…33 Although these results cannot directly be extrapolated to man, they are in line with the frequently reported jaw clenching and grinding of teeth during ecstasy use (50-89%).…”
Section: Bruxismsupporting
confidence: 81%
“…33 Although these results cannot directly be extrapolated to man, they are in line with the frequently reported jaw clenching and grinding of teeth during ecstasy use (50-89%).…”
Section: Bruxismsupporting
confidence: 81%
“…Ingestion of amphetamine derivatives has been associated with acute adverse reactions such as hyperthermia, hypertension, tachycardia, acute myocardial infarction and increased motor activities such as jaw clenching ( Hegadoren et al ., 1999 ; Cole & Sumnall, 2003a ). Consistent with clinical signs, animal studies have also shown increases in blood pressure, disruption in thermoregulation, inhibition of the jaw opening reflex and increased locomotor activity ( Gold et al ., 1988 ; Colado et al ., 1995 ; 1999 ; Daws et al ., 2000 ; Boules et al ., 2001 ; Arrue et al ., 2004 ). Furthermore, it has been demonstrated that repeated treatment with amphetamines in experimental animals can produce either tolerance or sensitization to their behavioural actions ( Foltin & Schuster, 1982 ; Kalivas et al ., 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary retention reported with MDMA ( McCann et al ., 1996 ) may also involve peripheral α ‐adrenoceptor‐mediated actions. The jaw clenching reported with the use of MDMA ( Hayner & McKinney, 1986 ; McCann et al ., 1996 ) may involve α 2 ‐adrenoceptor‐mediated inhibition of the jaw opening reflex ( Arrue et al ., 2004 ), presumably by a central action. Acute psychiatric complications of MDMA, including panic attacks ( McCann et al ., 1996 ), as well as temperature changes ( Bexis & Docherty, 2005 ), may also involve noradrenergic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the amphetamine‐like substance XTC reportedly has bruxism as a side effect (47). Based on a study with rats, Arrue et al (48) give a possible explanation for this side effect of XTC, viz. the XTC‐induced reduction of the jaw‐opening reflex.…”
mentioning
confidence: 99%